HUBUNGAN BUDAYA ORGANISASI DENGAN KINERJA PERAWAT PELAKSANA DI RAWAT INAP RS PMC - Iqbal, Muhammad; Agritubella, Syafrisar Meri (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Organizational culture is characteristic of the organization. It is associated with good or poor performance of nurses. Setbacks performance of nurses will have an impact on services provided. The aim of this research is to give a description the relationship between organizational culture with work of nurse performance in patients ward in PMC Hospital. The design of this research was descriptif correlational with cross sectional method to 49 subject of nurse with total sampling with inclusion criteria. The result of the study showed 69,4 % organizational culture is low and 71,4% nurse performance is low. The conclution of the study showed that their was significant relationship between organizational culture with nurse performance. The dominant variable that correlated with nurse performance were responsibility.